Effect of Particle Size and its Distribution on Rheological Behaviour of Coal-Water Slurry - Sahoo, Ganeswar; Routray, Anupama; Kumari Padhy, Mamata; K. Senapati, P. (International Journal of Engineering and Technology, 2018)
An experimental investigation has been conducted to study the rheological behaviour of coal-water slurry (CWS) of low rank coal. Different samples have been prepared by pulverizing it to powder form.Â Bi-modal and mono-modal samples have been prepared separately. Thereafter slurry was prepared by adding distilled water to the sample. CWS of different coal concentration have been prepared with particle size from 37 Âµm to 250 Âµm. The rheological behaviour of both mono-modal and bi-modal slurry have been investigated with help of HAAKE RHEO STRESS 1, a thermo scientific rheometer. Comparing the rheological behaviour of CWS prepared from bi-modal sample and mono-modal sample, it is observed that CWS from bimodal exhibit lower viscosity and shear stress compare to mono-modal sample. The stability of slurry prepared from bi-modal samples are found to be poor than mono-modal samples. The stability of coal sample below 75Âµm at different concentration has also been investigated. Also the characterization of coal sample has been done. It is observed that as the ratio of coarse particle decreases the shear stress and viscosity also decreases. Â Â